Law, politics and rights : essays in memory of Kader Asmal - Asmal, Kader; Maluwa, Tiyanjana (Martinus Nijhoff Publishers, 2013)
The essays in this collection, drawing upon Kader Asmal's inspirational role, explore various aspects of constitutionalism, human rights, democracy, and international criminal justice and the ICC, among other topics. Some of the discussions also offer accounts of Asmal's contribution to international law-making processes and legal activism.